When Ecolabeling is Not Enough: The Importance of Green Brand Awareness in Influencing Purchase Decisions - Venita Venita; Yulia Hamdaini Putri; Aslamia Rosa (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study investigates the impact of ecolabelling on college students' purchasing decisions for ecologically friendly paper products in Palembang City, with green brand awareness serving as a mediating variable. The applied methodology is quantitative, involving purposive sample approaches with 100 respondents who have previously purchased go green labeled paper. We employed SEM-PLS to examine the correlations among the variables in the data analysis. The research findings demonstrate that ecolabelling does not directly affect purchase decisions; yet, it significantly influences them through green brand awareness, indicating a total mediation effect. The findings indicate that eco-friendly labels are beneficial only when customers comprehend the significance of brand sustainability. This research highlights the need for corporations to augment education on ecolabels and to elevate environmental literacy via more informed and pertinent communication methods directed at the younger generation. Theoretically, this research reinforces signaling theory and green marketing theory within the context of environmentally conscious consumer behavior.